6.23. Wyznacz liczbę a wiedząc, że prosta m jest równoległa do prostej k. a) k: y = (2a – 3) * x + 4 , b) k: y = 3x + a , c) k: y = (1 – a) * x , d) k: y = 8 , m : y = – 4x + 7 m : y = 4 + (4 + a) * x m : y = (2a – 5) * x – 9 m: y = (a – 10) * x + 7 P i na

 6.23. Wyznacz liczbę a wiedząc, że prosta m jest równoległa do prostej k. a) k: y = (2a – 3) * x + 4 , b) k: y = 3x + a , c) k: y = (1 – a) * x , d) k: y = 8 , m : y = – 4x + 7 m : y = 4 + (4 + a) * x m : y = (2a – 5) * x – 9 m: y = (a – 10) * x + 7 P i na